2011
DOI: 10.1007/s13225-011-0110-4
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of fungal pathogens associated with grapevine trunk diseases in Arkansas and Missouri

Abstract: Grapevine trunk diseases are a major concern to the wine-and table-grape industries worldwide, limiting both vineyard longevity and productivity. Field surveys conducted throughout the grape-growing regions of Arkansas and Missouri revealed the presence of three economically important grapevine trunk diseases including, Botryosphaeria canker, Eutypa dieback and esca. Morphological studies along with multi-gene phylogenetical analyses confirmed the identification of 15 different fungal taxa associated with diff… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
72
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 134 publications
(75 citation statements)
references
References 45 publications
(55 reference statements)
3
72
0
Order By: Relevance
“…2 Artificial inoculation. The upper site is the control inoculated by sterilized PDA plug, and the two sites below show pathogenesis of the isolate NW11-016 after 2 weeks related (Sakalidis et al 2011) and this was confirmed here, and it is confusing to find both N. ribis (Urbez-Torres et al 2012) and N. parvum (Martos et al 2011) ever described as canker pathogen of Vitis vinfera.…”
Section: Resultssupporting
confidence: 70%
“…2 Artificial inoculation. The upper site is the control inoculated by sterilized PDA plug, and the two sites below show pathogenesis of the isolate NW11-016 after 2 weeks related (Sakalidis et al 2011) and this was confirmed here, and it is confusing to find both N. ribis (Urbez-Torres et al 2012) and N. parvum (Martos et al 2011) ever described as canker pathogen of Vitis vinfera.…”
Section: Resultssupporting
confidence: 70%
“…As discussed above, most studies investigating the incidence of dieback are either geographically restricted (Dakin et al 2010;McDonald & Eskalen 2011;Urbez-Torres et al 2012) or focusing on the occurrence of a single causative agent across a large area. This study aims to assess an expansive geographical range (incorporating most of parkinsonia's range within Australia), and assess the wide range of fungi associated with the occurrence of dieback.…”
Section: Referencesmentioning
confidence: 99%
“…The DUBOS, 2000;VICENT et al, 2001;HALLEEN et al, 2004;AROCA et al, 2006;HALLEEN et al, 2006a;HALLEEN et al, 2006b;MOSTERT et al, 2006;ZANZOTTO et al, 2007;REGO et al, 2009;ÚRBEZ-TORRES et al, 2012;BERTSCH et al, 2013;BILLONES-BAAIJENS et al, 2013;WHITELAW-WECKERT et al, 2013;LOMBARD et al, 2014). In addition to these species, new genera have been continuously reported in literature.…”
Section: New Diseases Transmitted By Vegetative Propagationmentioning
confidence: 99%